Applying the zoo model to conservation of threatened exceptional plant species. Issue 6 (17th June 2020) - Wood, Jordan; Ballou, Jonathan D.; Callicrate, Taylor; Fant, Jeremie B.; Griffith, M. Patrick; Kramer, Andrea T.; Lacy, Robert C.; Meyer, Abby; Sullivan, Sara; Traylor‐Holzer, Kathy; Walsh, Seana K.; Havens, Kayri
Abstract: Maintaining a living plant collection is the most common method of ex situ conservation for plant species that cannot be seed banked (i.e., exceptional species). Viability of living collections, and their value for future conservation efforts, can be limited without coordinated efforts to track and manage individuals across institutions. Using a pedigree‐focused approach, the zoological community has established an inter‐institutional infrastructure to support long‐term viability of captive animal populations. We assessed the ability of this coordinated metacollection infrastructure to support the conservation of 4 plant species curated in living collections at multiple botanic gardens around the world. Limitations in current practices include the inability to compile, share, and analyze plant collections data at the individual level, as well as difficulty in tracking original provenance of ex situ material. The coordinated metacollection framework used by zoos can be adopted by the botanical community to improve conservation outcomes by minimizing the loss of genetic diversity in collections. We suggest actions to improve ex situ conservation of exceptional plant species, including developing a central database to aggregate data and track unique individuals of priority threatened species among institutions and adapting a pedigree‐based population management tool that incorporates life‐history aspects unique to plants. If approached collaboratively across regional, national, and global scales, these actions could transform ex situ conservation of threatened plant species. Abstract : Article Impact Statement: Using zoo‐style studbooks and pedigree management will be transformative for the conservation of exceptional plants like Brighamia insignis . Abstract : Aplicación del Modelo Zoológico a la Conservación de Especies Excepcionales de Plantas Amenazadas Resumen: El mantenimiento de una colección de plantas vivas es el método más común para de conservación ex situ para especies de plantas que no pueden almacenarse en bancos de semillas (i. e., especies excepcionales). La viabilidad de las colecciones vivientes, junto con el valor que representan para los futuros esfuerzo de conservación, puede estar limitada si no existen esfuerzos coordinados para rastrear y manejar a los individuos entre las instituciones. Mediante una estrategia enfocada en el linaje, la comunidad de zoológicos ha establecido una infraestructura interinstitucional que respalda la viabilidad a largo plazo de las poblaciones de animales en cautiverio. Evaluamos la habilidad de esta infraestructura coordinada de metacolecciones para apoyar en la conservación de cuatro especies de plantas curadas en colecciones vivientes en varios jardines botánicos de todo el mundo. Las limitaciones de las prácticas contemporáneas incluyen la incapacidad de recopilar, compartir y analizar los datos de las colecciones de plantas a nivel individual, así como la dificultad de rastrear la procedencia original del material ex situ. El marco de trabajo de metacolecciones coordinadas que utilizan los zoológicos puede ser adoptado por la comunidad botánica para mejorar los resultados de conservación al minimizar la pérdida de la diversidad genética que ocurre en las colecciones. Sugerimos acciones que aumenten la conservación ex situ de las especies excepcionales de plantas. Estas acciones incluyen el desarrollo de una base de datos central para acumular datos y rastrear entre las instituciones a los individuos únicos de las especies amenazadas prioritarias y la adaptación de una herramienta de manejo poblacional basada en el linaje que incorpore los aspectos únicos de la historia de vida de las plantas. Si estas acciones se plantean colaborativamente a escala regional, nacional y global, podrían transformar la conservación ex situ de las especies amenazadas de plantas. 摘要: 保存植物活体是对不能贮存种子的植物 (特殊植物) 最常用的迁地保护方法。然而, 如果没有跨机构的生物个体跟踪和管理的协作, 活标本的生存能力及其对未来保护工作的价值可能会受到限制。动物保护团体利用基于系谱的方法建立了一套跨机构的基础工具来支持圈养动物种群的长期生存。本研究评估了这种协作性的聚合采集基础工具在支持保护四种在全球多个植物园存有活标本的植物的能力。结果表明, 当前的保护实践的局限性包括无法在生物个体水平汇编、分享和分析采集植物的数据, 以及难以追踪迁地保护植物的原始种源。植物保护团体可以采用动物园使用的协作性聚合采集框架, 通过减少采集过程中遗传多样性丧失来改善保护结果。我们建议采取行动来推动特殊植物物种的迁地保护, 包括建立中央数据库来收集数据、追踪保护机构优先保护的受威胁物种的每个个体, 以及开发基于系谱的、整合植物特有生活史信息的种群管理工具。如果在区域、国家和全球范围内进行协作, 这些行动将改变濒危植物物种的迁地保护现状。 【翻译: 胡怡思; 审校: 聂永刚】